The Concept of God's Timelessness Affects Religious Beliefs - Pane, Exson Eduaman (Jurnal Koinonia: Fakultas Filsafat Universitas Advent Indonesia, 2025)
This research examines the concept of timelessness and its significant implications for religious beliefs, focusing on theological, ethical, and spiritual dimensions. Employing a qualitative methodology, the study analyzes theological texts, ethical frameworks, and spiritual practices across various religious traditions to explore how the attribute of timelessness shapes believers' understanding of the divine. Timelessness, as an attribute of God, emphasizes His eternal and unchanging qualities, influencing believers’ perceptions of their relationship with the divine and fostering a sense of intimacy and transcendence. Ethically, the belief in a timeless God provides a framework for moral decision-making, reinforcing the idea of absolute truths rooted in divine will. This perspective cultivates a sense of responsibility and accountability among believers, shaping their concepts of justice and mercy. Spiritually, the concept of timelessness impacts practices such as prayer, worship, and meditation, encouraging individuals to seek experiences of transcendence and connection with the eternal. Mindfulness and contemplative practices allow believers to cultivate a sense of presence that enriches their spiritual lives. The implications of timelessness on religious beliefs are profound, influencing theological understandings, ethical frameworks, and spiritual practices. Engaging with the concept of timelessness invites believers to explore the depths of their faith and spirituality, recognizing the connection between the eternal and the temporal. This research highlights the importance of timelessness in fostering a deeper sense of connection, purpose, and meaning in the lives of believers, encouraging a holistic approach to faith that transcends the confines of time.